Simultaneous Extraction and Determination of 5-Hydroxy tryptophol and 5-Hydroxyindol-3-acetic Acid in Urine of Alcoholism by HPLC with Fluorescence Detection - Ramezani, Z.; Kalantari, H.; Negahbani, H.R. (Asian Journal of Chemistry, 2010)
5-Hydroxy tryptophol (5-HTOL) and 5-hydroxyindol-3-acetic acid (5-HIAA), two serotonin metabolite, were derivatized with benzylamine at room temperature in a mixture of 0.3 M 3-cyclohexylamino-1-propane sulfonic acid (CAPS buffer, pH 12) and methanol in presence of potassium hexacyanoferrate(III), which produce highly fluorescent benzoxazole derivative. The resulting species were separated on XDB C18 (150 mm × 4.6 mm, 5 μm) with isocratic elution using a mixture of methanol and 15 mM acetate buffer (pH 4.5) containing 1 mM octansulfonic acid and acetonitrile as modifier (65:35). They were detected spectroflourometrically at 480 nm with excitation wavelength of 345 nm. Urine samples of ethanol positive (alcoholism) were collected from 20 persons sent to forensic medical center toxicology laboratory, Tehran, Iran. Sixty urine samples of ethanol negative persons were also collected. 5-Hydroxy tryptophol and 5-hydroxyindol-3-acetic acid contents were determined after liquid-liquid extraction and derivitazation. The mean value of 5-HTOL/5-HIAA ratio for ethanol positive and negative samples was 74.25 and 2.19 pmol/nmol, respectively. The cut off value was 10.7 pmol/nmol.